ANALISIS PERBANDINGAN MODEL SPRINGATE DAN ALTMAN Z-SCORE TERHADAP POTENSI FINANCIAL DISTRESS SEKTOR PROPERTI & REAL ESTATE DI INDONESIA TAHUN 2018-2022 - Hesi, Titia; Zelmiyanti, Riri (Pusat P2M Politeknik Negeri Batam, 2024)
This research compares the predictive of the Springate model and the Altman Z-Score models for possible financial distress in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) between 2018-2022 is compared. Purposive sampling was used to choose of 12 companies from a population 25 companies, with a total of 60 data. The Paired Sample T-Test is used for comparative analysis, along with the IBM SPSS Version 22 application. The results indicate a significant difference between the two models, attributed to variations in the ratios used for calculation. The Altman Z-Score model shows higher accuracy, with a presentation of 91,67%, compared to the Springate model's accuracy of 83.3%. This indicates that the Altman Z-Score model is more proficient in predicting potential financial distress among property and real estate sector companies listed on the IDX.